Pengaruh Independensi, Pengalaman Kerja, Komitmen Organisasi, dan Motivasi Auditor Pada Kualitas Audit - Mardika, Ida Bagus Angga; Suartana, I Wayan (E-Jurnal Akuntansi, 2019)
The aims of the current study are to determine the effect of independence, work experience, organization commitment, an d auditor’s motivation towards audit quality of the auditor i n Inspectorate of Bali Province. The population of this study were all functional position auditor and all officials of local government affairs in Inspectorate of Bali Province and the sampling method was using saturated or census sample method. The numbers of samples used were 41 respondent s. The data were collected by questionnaire measured by likert scale. The result of the current study shows that independence , work experience, organization commitment, an d auditor’s motivation have a positive and significant impact towards audit quality in Inspectorate of Bali Province. Keyword: Independence, work experience, organization commitment, auditor’s motivation, audit quality.